Self-Awareness and Quality of Life in Menopausal Women: A Concept Analysis - Noorma, Nilam; Hapsari, Ririn; Aisah, Siti; Vranada, Aric (Health & Medical Sciences, 2025)
This study aims to clarify the concept of self-awareness in menopausal women and examine its relationship with quality of life (QoL) using Walker and Avant’s concept analysis framework. The analysis included articles published between 2021 and 2025, retrieved from databases such as Google Scholar, ProQuest, PubMed, CINAHL, and Science Direct, using keywords “menopause,” “self-awareness,” “quality of life,” and “concept analysis.” The findings reveal that self-awareness in menopausal women comprises interoceptive awareness, cognitive insight, emotional recognition and regulation, health literacy, and adaptive behavioral responses. Antecedents of self-awareness include health literacy, access to information, emotional support, mindfulness experience, and motivation for self-care. Its consequences involve improved symptom management, adaptive coping, reduced anxiety and depression, and enhanced physical, psychosocial, and sexual QoL. Empirical referents identified include MENQOL, MRS, MAAS, MAIA, symptom diaries, and outcomes of mindfulness or self-awareness interventions. The study concludes that self-awareness is a multidimensional construct essential for improving the QoL of menopausal women. Clarifying this concept establishes a theoretical foundation for developing targeted nursing interventions, standardized measurement tools, and future research exploring mechanisms linking self-awareness to QoL.